(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: MR (Measles Rubella) campaign is one of Indonesia’s efforts to achieve the world target without measles, rubella, and Congenital Rubella Syndrome (CRS) in 2020. However, the results show that MR campaign immunization coverage is not optimal. This study aims to determine whether the knowledge of mothers about rubella is related to MR immunization status in MR campaign at Java Island. Method: This cross-sectional study used secondary data from the survey of Independent Evaluation of MR Immunization in 6 provinces at Java Island in 2017. There were 5,971 samples of mothers who had children aged 9-59 months were obtained based on cluster sampling technique. Bivariate and multivariate analysis were used to see the relationship between mother’s knowledge of rubella and MR immunization status. Result: Mother’s knowledge about rubella interacted with belief (POR 1,899 95% CI 1,267-2,848) and interacted with education (POR 1,675 95% CI 1,086-2,583) to form a statistically significant relationship with MR immunization status. Conclusion: Mother’s knowledge of rubella is very important in increasing MR immunization coverage. Therefore, the government is expected to cooperate with active stakeholders to provide information on MR immunization.